Factores nutricionales y rendimiento académico de estudiantes de la Facultad de Industrias Alimentarias de la Universidad Nacional de la Amazonía Peruana - Flores Yumbato, Andrea del Carmen (2025)
The purpose of this study was to determine the relationship between nutritional factors and academic performance in students of the Faculty of Food Industries of the National University of the Peruvian Amazon. The methodology used in the research was developed under a quantitative, descriptive, non-experimental, correlational-cross-sectional approach, having 214 university students as a study sample. Data were collected through the lifestyle questionnaire, SISCO, a survey of sociodemographic factors and a nutritional sheet. The statistical analysis was carried out using SPSS V.25 and the RHO Spearman correlation test was used to determine if there is a relationship between the variables. The results indicate that in the sociodemographic factors, 54.7% of students are between 18 and 20 years old, 97.2% have a single marital status, as well as 90.6% come from the urban area, 86.7% still live with their mother, father and siblings, on the other hand, 93.5% do not have any morbidity, 84.6% do not have a job, 75.6% finance their studies with the help of their parents or other relatives, 61.1% have an unhealthy lifestyle, in addition, 52.3% of students have a severe stress level, 55.2% have a normal BMI, 76.8% have a low cardiometabolic risk, and finally, 78% have a regular academic performance. It is concluded that no statistically significant relationship was found between nutritional factors and the academic performance of students of the Faculty of Food Industries.